Characterization of Silicon Carbon Nitride for Low Temperature Wafer-to-Wafer Direct Bonding. (8th September 2020) - Nagano, Fuya; Iacovo, Serena; Phommahaxay, Alain; Inoue, Fumihiro; Sleeckx, Erik; De Gendt, Stefan; Beyer, Gerald; Beyne, Eric
Abstract : Silicon carbon nitride (SiCN) compounds have aroused great interest as dielectric materials for direct bonding because of the high thermal stability and high bond strength, as well as its Cu diffusion barrier properties. While wafer-to-wafer direct bonding, including the dielectric deposition step, is generally performed at high temperature (>350°C), applications such as heterogeneous chips and DRAMs would require wafer-to-wafer direct bonding at lower temperature (<250°C). In this study, we evaluate, for SiCN deposited at various temperatures, the impact for direct wafer bonding of lowering the temperature of all processes. Chemical and mechanical properties of SiCN direct bonding are studied.